(3JfbjM GdaUhd aj Yde GdCUhds - (3CHhGdYHGS TgGH GdOjf CMeO Hf GOQjS Hf YHO GdQMef GdUfgGLj GdbQGaj GdeGdcj,J (B684 (3g` s ((3CHh HcQ Hf UGQe s)
(3ChdgG (B:s
(3eG HYO aEf gPG cJGH LeYJ ajg eSGFd GdeMUhd ddEeGe aNQ GdOjf hCVaJ Edjg eSGFd cJH GdEaGOI ddbGVi YHO GdhgGH GdeGdci GdHGH GdChd ai GdEUWdGMGJ s
(3BNQgG (B:s
(3GdJCOjH hGdRLQ EeG ebOQg cGdMOhO Ch ZjQ ebOQI cGdJYRjR ajfHZi ddabjg GdEMWI HgG dJSCdI GdaQhb hGdeOGQc ai GdaQhY hgPG BNQg hGddg JYGdi gh GdeYjf Ydi GdNjQ cdg hgh MSHfG hfYe Gdhcjd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B94 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B158s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B499s
Keywords: (3CUhd Gdabgs